An introduction to tree-ring dating / (Acc. 4338) - Stokes, Marvin A.; Smiley, Terah L. (Terah Leroy), 1914- (Tucson : University of Arizona Press, 1996)
Tree-ring dating, or dendrochronology, is the study of the chronological sequence of annual growth rings in trees. This book--a seminal study in its field--provides a simple yet eloquent introduction to the discipline, explaining what a dendrochronologist does both in the field and in the laboratory. Authors Stokes and Smiley first explain the basic principles of tree-ring dating, then describe details of the process, step by step, from the time a sample is collected until it is incorporated into a master chronology. The book focuses on coniferous evergreens of the Southwest, particularly piAons, because they have wide geographic distribution, constitute a large population, and show excellent growth response to certain controlling factors. The book is specifically concerned with the task of establishing a calendar date for a wood or charcoal specimen. This concise but thorough explication of an important discipline will make dendrochonology more meaningful to students and professionals in archaeology, forestry, hydrology, and global change.
Keywords: Dendrochronology